Professional Knowledge and Educational Restructuring in Europe - Goodson, Ivor F.; Lindblad, Sverker; SpringerLink (Online service) (Rotterdam : SensePublishers, 2011)
European welfare institutions such as education and health care are restructuring their organisations in terms of decentralisation, deregulation, privatization and so forth. As a consequence professional positions and demands on professional competencies in these institutions are in transition. At the same time European societies are changing in different ways, e.g. in terms of a "knowledge society" as well as in demographic and cultural changes. Professionals such as teachers and nurses are meeting such changes in their work with students and clients.Thus, there is a need to study these transitions and changes. Here we are doing this from a "bottom-up" perspective where we are comparing experiences in different institutional and national contexts. This study combines two kinds of narrative research; a study of the systemic narratives produced by governments who are restructuring educational systems and the life history narratives of those professionals working within those systems and their perspectives on ongoing restructuring.
Keywords: Education; Education; Professional & Vocational Education